2021
DOI: 10.1093/bib/bbab341
|View full text |Cite
|
Sign up to set email alerts
|

Improved protein contact prediction using dimensional hybrid residual networks and singularity enhanced loss function

Abstract: Deep residual learning has shown great success in protein contact prediction. In this study, a new deep residual learning-based protein contact prediction model was developed. Comparing with previous models, a new type of residual block hybridizing 1D and 2D convolutions was designed to increase the effective receptive field of the residual network, and a new loss function emphasizing the easily misclassified residue pairs was proposed to enhance the model training. The developed protein contact prediction mod… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…The first subnet, the conversion subnet, includes a conversion block that converts 1D features to 2D matrices. Unlike the outer concatenation approach used in most existing models 18,20 to convert 1D features to 2D matrices, our conversion method eliminates the repetition of information, and more importantly, it is learned during the training process, rather than preprocessed. To do so, the model learns the best-converted matrix for each 1D feature (SI Figure S2).…”
Section: Cgan-cmap Architecturementioning
confidence: 99%
See 2 more Smart Citations
“…The first subnet, the conversion subnet, includes a conversion block that converts 1D features to 2D matrices. Unlike the outer concatenation approach used in most existing models 18,20 to convert 1D features to 2D matrices, our conversion method eliminates the repetition of information, and more importantly, it is learned during the training process, rather than preprocessed. To do so, the model learns the best-converted matrix for each 1D feature (SI Figure S2).…”
Section: Cgan-cmap Architecturementioning
confidence: 99%
“…Notably, DCA methods generally exhibit two major limitations. First, DCA-based methods have poor performance when the number of homologous sequences is lower than approximately 50 17,18 . Second, these methods extract only linear relationships between pairs of residues 17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The input features are then transformed by the dimensional hybrid residual network formed by dimensional hybrid residual blocks (1D2D blocks). A detailed description of the 1D2D block can be found in (Si and Yan, 2021) 20 . In this study, we increased the length of the 1D convolution kernels from 9 to 15, for we found using the longer 1D kernels slightly improved the model performance.…”
Section: Overview Of Drn-1d2d_inter 11 the Model Of Drn-1d2d_intermentioning
confidence: 99%
“…The structural information enriched features obtained from protein language models were further combined with traditional statistical features including position-specific scoring matrices (PSSM) and inter-protein coevolution to form the input features of our prediction model, which were then transformed by the residual network formed by dimensional hybrid residual blocks to predict inter-protein contacts. It was shown in our previous study that the application of the dimensional hybrid residual blocks can increase the effective receptive field of the residual network, and thus improve the model performance 20 . The developed model referred to as DRN-1D2D_Inter was extensively benchmarked on PPI dataset including both homomeric PPIs and heteromeric PPIs.…”
Section: Introductionmentioning
confidence: 97%